Numerical study for atmospheric transport of radioactive materials for hypothetical severe nuclear accident under different meteorological conditions - Ma, Zhenhui; Li, Zhiming; Tang, Xiuhuan; Liu, Longbo; Bao, Lihong; Su, Chunlei; Li, Da; Wang, Baosheng; Zhangsun, Yonggang; Hu, Pan; Ma, Tengyue; Chen, Lixin (Frontiers in Environmental Science, 2024)
Study for atmospheric transport is essential for consequence assessment of severe nuclear accident, since radionuclides could be released from nuclear facility into atmosphere, and cause radioactive pollution in environment. Atmospheric transport behaviors are strongly related with meteorological conditions, which can obviously influence transport and diffusion characteristics of radioactive materials in atmosphere, thus it is meaningful to investigate the coupling effects between meteorological processes and transport behaviors of radioactive materials. In this paper, so as to evaluate the influence of meteorological conditions on atmospheric transport, meteorological parameters for different seasons were firstly acquired by weather research forecast model. Furthermore, atmospheric transport behaviors of radioactive materials were simulated by meso-scale numerical model under different meteorological conditions, and numerical analysis were conducted towards transport and deposition behaviors of radioactive materials. Besides, the influence of FDDA (Four Dimensional Data Assimilation) on meteorological parameters and atmospheric transport behaviors were researched in the paper. The present study is important for strengthening consequence assessment under severe nuclear accident, and made it possible to apply data assimilation technology in the further research work.